OP65 The effects of pedometer and other step-count monitoring interventions on physical activity: a systematic review and meta-analysis of randomised controlled trials. (3rd September 2019) - Chaudhry, UAR; Wahlich, C; Normansell, R; Knightly, R; Cook, D; Harris, T
Abstract : Background: Physical inactivity is a growing public health concern, and the fourth leading cause of death globally. Pedometers measure step-counts and can increase physical activity levels. Newer devices, for example mobile phone applications and body worn devices, also measure step-counts and require scrutiny of their effectiveness. Our primary aim is to conduct a systematic review and meta-analysis of the effects of pedometer and other step-count monitoring interventions on physical activity levels among the adult general population. Methods: We systematically searched seven databases using MeSH headings and keywords to identify randomized controlled trials published after 1/1/2000. We included trials with healthy adults participants aged ≥18, or those at risk of disease. Children, those selected with a specific health condition, high-performance trainers and hospital-based studies were excluded. The intervention group comprised community-based step-count monitoring interventions including pedometers with objective physical activity measures; the comparator group incorporated 'usual standard care' or healthcare advice with minimal active engagement. The primary outcome was change in step-count at follow-up compared to baseline. A random-effects model was utilized to assess the primary outcome, and a risk of bias assessment determined the quality of included studies. The protocol is registered PROSPERO: CRD42017075810. Results: Following initial database searching of 14, 356 records and subsequent forward citation search, 54 studies were included, of which 13 were part of the narrative synthesis. 41 studies were therefore incorporated in the quantitative meta-analysis; 22 providing estimated mean between-group differences in change from baseline step-count and 19 providing mean between-group differences in end-point only step-counts. From the 22 studies, 16 reported the primary outcome at ≤3 months with a mean difference (MD) in step-count of 1255 [95% Confidence Interval 848, 1661]; 8 studies at ≤6 months, MD 1084 steps [647, 1520]; 9 studies at ≤1 year, MD 516 steps [273, 758]; 2 studies at ≤2 years, MD 290 steps [-7, 587]; and 4 studies at >2 years, MD 494 steps [251, 738]. The 19 studies with end-point only step-counts highlighted similar findings, but had fewer participants and reported no outcomes beyond one year. Discussion: This review demonstrated that pedometers and other step-count monitoring interventions significantly increase individuals' step-counts in the short-term, with larger trials also showing small sustained long-term effects. These interventions could therefore provide a means of addressing the public health inactivity challenge. Further work will evaluate which type of interventions are more effective and determine the effect-modifiers of physical activity maintenance.